Allostery‐driven changes in dynamics regulate the activation of bacterial copper transcription factor. (12th April 2022) - Yakobov, Idan; Mandato, Alysia; Hofmann, Lukas; Singewald, Kevin; Shenberger, Yulia; Gevorkyan‐Airapetov, Lada; Saxena, Sunil; Ruthstein, Sharon
Abstract: Metalloregulators bind and respond to metal ions by regulating the transcription of metal homeostasis genes. Copper efflux regulator (CueR) is a copper‐responsive metalloregulator that is found in numerous Gram‐negative bacteria. Upon Cu(I) coordination, CueR initiates transcription by bending the bound DNA promoter regions facilitating interaction with RNA polymerase. The structure of Escherichia coli CueR in presence of DNA and metal ion has been reported using X‐ray crystallography and cryo‐EM, providing information about the mechanism of action. However, the specific role of copper in controlling this transcription mechanism remains elusive. Herein, we use room temperature electron paramagnetic resonance (EPR) experiments to follow allosterically driven dynamical changes in E. coli CueR induced by Cu(I) binding. We suggest that more than one Cu(I) ion binds per CueR monomer, leading to changes in site‐specific dynamics at the Cu(I) binding domain and at the distant DNA binding site. Interestingly, Cu(I) binding leads to an increase in dynamics about 27 Å away at the DNA binding domain. These changes in the dynamics of the DNA binding domain are important for exact coordination with the DNA. Thus, Cu(I) binding is critical to initiate a series of conformational changes that regulate and initiate gene transcription. Broad audience statement: The dynamics of metal transcription factors as a function of metal and DNA binding are complex. In this study, we use EPR spectroscopy to measure dynamical changes of Escherichia coli CueR as a function of copper and DNA binding. We show that copper controls the activation of the transcription processes by initiation a series of dynamical changes over the protein.